2020
DOI: 10.1111/bph.14957
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of cilastatin against diclofenac‐induced nephrotoxicity through interaction with diclofenac acyl glucuronide via organic anion transporters

Abstract: Background and Purpose: Diclofenac is a widely used nonsteroidal antiinflammatory drug. However, adverse effects in the kidney limit its clinical application. The present study was aimed to evaluate the potential effect of cilastatin on diclofenac-induced acute kidney injury and to clarify the potential roles of renal organic anion transporters (OATs) in the drug-drug interaction between cilastatin and diclofenac. Experimental Approach: The effect of cilastatin was evaluated in diclofenac-induced acute kidney … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Oxidative stress-mediated apoptosis of kidney tubular cells is recognized as a fundamental mechanism in kidney injury (29). Huo et al have shown that inhibiting apoptosis and reducing inflammation may ameliorate diclofenac-induced AKI in mice (46). We exhibited that BMSCs inhibited RTEC apoptosis in rats with SI-AKI.…”
Section: Discussionmentioning
confidence: 67%
“…Oxidative stress-mediated apoptosis of kidney tubular cells is recognized as a fundamental mechanism in kidney injury (29). Huo et al have shown that inhibiting apoptosis and reducing inflammation may ameliorate diclofenac-induced AKI in mice (46). We exhibited that BMSCs inhibited RTEC apoptosis in rats with SI-AKI.…”
Section: Discussionmentioning
confidence: 67%
“…OAT1 and OAT3 transport some glucuronide and sulfate conjugates of endogenous compounds and xenobiotics, but only a small number of drug conjugates have been identified as their substrates ( Table 1 , Supplementary Table S1 ). Morinidazole-S, edaravone-S and diclofenac-AG are transported by both OAT1 and OAT3 ( Mizuno et al, 2007a ; Zhong et al, 2014 ; Zhang et al, 2016 ; Huo et al, 2020 ). On the other hand, OAT3, but not OAT1, transports ethinylestradiol-S and glucuronides such as of cabotegravir-G, curcumin-G, genistein-7-G, steviol-G and MPA-G ( Uwai et al, 2007 ; Han et al, 2010a ; Wong et al, 2011b ; Wang M. et al, 2015 ; Zhou et al, 2017 ; Patel et al, 2019 ).…”
Section: Transport Of Glucuronide and Sulfate Conjugatesmentioning
confidence: 99%
“…Rabbit primary proximal tubule cells were isolated from male rabbits by the previous method with minor modifications (Huo et al, 2020). Briefly, rabbits were anesthetized with diethyl ether, and kidneys were perfused with Ca 2+ free Hank's buffer (pH 7.4) containing 25 mmol/L HEPES (HBSS) to remove blood, and then kidneys were removed and minced in a sterile cell culture dish on ice.…”
Section: Methodsmentioning
confidence: 99%